Sosialisasi Dan Kegiatan Mbkm Pembuatan Etilen Dari Limbah Pinang Betara Di Desa Laboratorium Terpadu, Kelurahan Mekar Jaya, Kabupaten Tanjung Jabung Barat - Revis Asra; Anis Tatik Maryani; Muazza; Sabrina Rahayu; Arikah Febrianti; Yogi Irawan Pandiangan; Sopnita Bestari; Febriyanti Munthe (Jurnal Pembangunan Berkelanjutan, 2023)
Betara Areca nut (Areca catechu Var. Betara) is a superior variety of areca nut in West Tanjung Jabung District, Jambi Province, which is marketed in various local markets in the province and exported to various countries, such as India and Pakistan. Most people in this area own an areca nut farming business and it is the main source of income for farming households compared to activities in fields other than areca nut farming. However, in running this business, farmers experience obstacles, one of which is the lack of continuity in betel nut production. There are times when areca nut trees are less fruitful and even some areca nuts stop bearing fruit. This is due to farmers' lack of knowledge of the ethylene hormone. While the source for the production of ethylene hormone is in their own environment. Utilization of this natural ethylene hormone can stimulate and increase areca nut fruit. In addition, the fruit ripening process will be faster if using this natural ethylene hormone. The potential of areca nut waste such as fronds, leaves, and coir as a source of natural ethylene is not utilized by the community. This is due to the lack of knowledge possessed by the community. Community Service activities in the Integrated Laboratory Village have been carried out, with the stages of socialization of the use of ethylene hormones from areca nut waste. The activity was attended by the head of the RT, several residents and students involved in Merdeka Learning Campus Merdeka (MBKM). Socialization has been conducted using the lecture method and opening up opportunities for the community to ask questions